REGULATION, AN EDUCATIONAL ACTION AT THE CROSSROADS OF KNOWLEDGE CONSTRUCTION: CASE OF PHYSICAL EDUCATION - ATOUN, Carlos Eméry Hyacinthe; AGBODJOGBÉ, Basile D; OGUEBOULE, BARA; YENOU, Richard; ATTIKLEME, Kossiv (My University, 2023)
As part of this study, the objective is to show the importance of regulation in the process of constructing knowledge in PE (Physical Education). To achieve this objective, we conducted a survey targeting PE teachers and students. The essential results from our investigations revealed that regulation is an essential didactic action for the construction of knowledge in PE. This is what Chevallard (2018) confirms when he shows that regulations are “gestures of aid to the study”. Thus, we can remember that regulation is a didactic action which further promotes the construction of knowledge in PE. In this perspective, the data from the filmed sessions, pre-session and post-session interviews with teachers and students were interpreted and analyzed using the concepts mobilized by Sensevy's theory of joint action (2007).
Keywords: Regulation; didactic action; construction of knowledge and PE